From physical to digital: investigating consumer behaviour of switching to mobile wallet - Alaeddin, Omar; Altounjy, Rana; Zainudin, Zalina; Kamarudin, Fakarudin (Czestochowa University of Technology, 2018)
Even though the digital payment methods are taking the intention of scholars nowadays as new trend to investigate it, there are still few studies that examine the consumer switching decision from the traditional way to digital way while performing the payments. Besides, the monetary market has some substitution effects; as users care about security, ease to use and the wide acceptance for the payment method they are using. The main aim of this research is to investigate the witching attitude and intention from the traditional payment by using the bank notes, debit or credit card or what called physical wallet to digital one by using mobile apps for doing payments. In total, 140 surveys were emailed to UNIKL business school’s staff, 98 questionnaires were returned fully answered and able to use. The results showed that perceived usefulness and perceived ease of use are effective factors into consumer attitude towards switching. Moreover, the relation between the attitude and the intention is significant while the perceived risk pull down the level of this effect.